The roles of brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) in predicting treatment remission in a Chinese Han population with generalized anxiety disorder. (January 2019) - Shen, Zhongxia; Zhu, Jianying; Yuan, Yonggui; Ren, Lie; Qian, Mincai; Lin, Min; Cai, Min; Zhang, Zhen; Shen, Xinhua
Highlights: The serum BDNF levels were lower in GAD patients than in healthy controls. The serum GDNF levels were also lower in GAD patients than in healthy controls. BDNF/GDNF level was negatively correlated with baseline HAMA score. BDNF level was positively correlated with GDNF level. Both baseline BDNF/GDNF levels in remissions and non-remissions had no statistically significant difference. No significant correlation was found between baseline BDNF/GDNF level and HAMA reduction rate. Abstract: Neurotrophic factors, particularly brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF), are involved in neuroplasticity in the nervous system. To explore the characteristics of BDNF and GDNF and their roles in predicting treatment remission in a Chinese Han population with generalized anxiety disorder (GAD), 85 GAD patients were treated with escitalopram or venlafaxine randomly for 8 weeks. The serum BDNF/GDNF levels were detected, while Hamilton Anxiety Rating Scale (HAMA) scores were measured at baseline and after 8 weeks of treatment. The differences in serum BDNF/GDNF levels between GAD patients ( n  = 85) and healthy controls ( n  = 73) and between remission and nonremission were then compared. The serum BDNF levels were lower in GAD patients (1197.24 ± 367.41 µg/L) than in healthy controls (1378.09 ± 382.46 µg/L) ( P  < 0.05). The serum GDNF levels were also lower in GAD patients (10.19 ± 9.86 µg/L) than in healthy controls (13.73 ± 9.44 µg/L) ( P  < 0.05). The BDNF level was negatively correlated with baseline HAMA score ( P  < 0.05). The GDNF level was negatively correlated with baseline HAMA score ( P  < 0.05). The BDNF level was positively correlated with GDNF level ( P  < 0.05). Both baseline BDNF/GDNF levels in remission and nonremission showed no statistically significant differences. No significant correlation was found between baseline BDNF level and the HAMA reduction rate or between baseline GDNF levels and the HAMA reduction rate. Both serum BDNF and GDNF were demonstrated to be potential biomarkers of GAD, it seems that serum BDNF and GDNF levels can be used to assess the baseline anxiety severity of GAD but cannot serve as a factor to predict treatment remission.